“Man as a Debtor”: Introduction to the Problem (on the Material of the Mahabharata) - Asafaylo, Marina P. (Opción, 1970)
Based on the ancient Indian epos The Mahabharata, this paper analyzes the idea according to which man is born an obligor. Man, in accordance with the provisions of Brahmanism, is burdened from birth with four basic duties – “duty to the gods”, “duty to the ancestors”, “duty to the sages”, “duty to people”. This thinking is part of the ancient Indian culture and largely determines its nature and specificity. The text of the Mahabharata for the most part is of a didactic nature, full of calls for the fulfillment of “one’s duty”, which is understood mainly as debt obligations related to the varna position of a person. These debts have a socio-political, religious and moral character and do not have a direct bearing on economic relations in society. Thus, each varna must perform a strictly defined circle of duties, ensuring the functioning of society on the whole. The article is concerned with a concept that is central in the ancient Indian religious and mythological worldview – dharma, which is directly connected with the idea of man as a debtor. The Mahabharata contains several words to clarify the “state of duty” of a person – dharma, ṛṇa, “indebted person” - ṛṇin, vrata, kārya. The relationship between the “four debts” and the “four stages of life” is investigated. The “state of being indebted” obtained from their birth is revealed to man through “the system of duties” at different stages of life. Dharma as a debt is also found in the doctrine of the “three life goals” (trivarga). It is concluded that for a person of ancient Indian culture, life outside the “debt system” is completely undesirable since their fulfilment leads to the path the goal of which is “liberation” (moksa).